Russian Para-Military Operations in Africa: The Wagner Group as a De Facto Foreign Policy Instrument - Neethling, Theo (Scientia Militaria - South African Journal of Military Studies, 2023)
As a Russian private military company, the Wagner Group has become an increasingly significant instrument in the Kremlin’s foreign policy toolkit. Wagner can even be described as a quasi-state actor and a proxy institution of the Russian state. It has a footprint across the globe, but its operations have especially been mired in controversy on the African continent. In Africa, Russia has sought to expand its geo-political influence and accordingly challenges Western influence on the continent. What is of particular interest is that Wagner’s operations are conducted in resource-rich and fragile African states where insecurity or conflict prevails. In view of the above, the study on which this article reports, examined the Wagner Group as a foreign policy instrument of the Russian government. The discussion commences with a background section on instruments of foreign policy, followed by an overview of Wagner’s activities worldwide, and particularly in Africa. Wagner’s operations in four African states are specifically analysed, namely Libya, the Central African Republic, Sudan, and Mali.